2009
DOI: 10.1364/ol.34.003821
|View full text |Cite
|
Sign up to set email alerts
|

Double-locked semiconductor laser for radio-over-fiber uplink transmission

Abstract: The nonlinear dynamics of an optically injected semiconductor laser are explored for radio-over-fiber uplink transmission. Under optical injection locking, the laser at the base station is operated in the period-one oscillation state, where its intensity oscillates at a tunable microwave frequency. When the oscillation is tuned to the subcarrier frequency, it is further locked by the uplink microwave signal. By simply using an ordinary 2.5-Gbps-grade semiconductor laser, uplink transmission of the phase-shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Owing to the redshifted cavity resonance enhancement, the lower oscillation sideband is typically much stronger than the upper one. These unique characteristics of the P1 dynamics have attracted increasing research interest for applications in optical signal processing [8][9][10] and photonic microwave generation [11][12][13][14][15][16][17][18] and transmission [19][20][21]. Recently, by taking advantage of the intensity asymmetry between the oscillation sidebands, Hung et al demonstrated that optical double-sideband modulation signals typically generated through direct or external modulation in RoF links can be converted into optical single-sideband modulation signals to mitigate the microwave power fading effect [22].…”
mentioning
confidence: 99%
“…Owing to the redshifted cavity resonance enhancement, the lower oscillation sideband is typically much stronger than the upper one. These unique characteristics of the P1 dynamics have attracted increasing research interest for applications in optical signal processing [8][9][10] and photonic microwave generation [11][12][13][14][15][16][17][18] and transmission [19][20][21]. Recently, by taking advantage of the intensity asymmetry between the oscillation sidebands, Hung et al demonstrated that optical double-sideband modulation signals typically generated through direct or external modulation in RoF links can be converted into optical single-sideband modulation signals to mitigate the microwave power fading effect [22].…”
mentioning
confidence: 99%
“…On the other hand, P1 oscillations have been used for the generation of photonic microwaves that can be continuously tuned over a very large frequency range, as well as for AM-to-FM signal conversion and remote target detection [23,24]. As a consequence of that, the external control technique of free-running lasers through optical injection-locking has recently been implemented in several state-of-the-art applications including millimetre-and microwave-wave generation [25][26][27][28], all optical signal processing [29], radio over fiber [30,31], cable access TV (CATV) [32] and low phase noise tunable photonic oscillators for time frequency applications [33,34]. Let us stress that P2 dynamics of the laser can also be used for accurate photonic microwave frequency conversion [35] for demultiplexing an individual channel in an optical time division multiplexing system.…”
Section: Application To the Extraction Of The Dynamical Properties Ofmentioning
confidence: 99%
“…Under external perturbations, semiconductor lasers (SLs) can exhibit various nonlinear dynamical behaviors, such as the period one (P1), period two (P2), multi-period (MP), and chaos (CO) etc. [1][2][3][4][5], which has attracted much attention due to their potential applications in photonic microwave amplifiers [6], optical frequency converters [7], wireless optical fiber communication [8], all-optical logic gates [9], laser Doppler velocimeters [10], secure optical communication, and random bit generation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%